Executive Committee Minutes 2012-10-04 - Academic Senate:::::::::
Agenda Approved. Minutes delayed. Chair Report. M.A. in Spanish revision approved as Senate consent item. President Report. Posthumous MA degree request for Marcia K. Brown approved for Senate agenda. Questions for the Provost. Vice Chair Report. Proposed GE Experimental Course process and form approved for Senate agenda. MBA revision approved as Senate consent item. Vice President of Administration and Finance Report. EPC Report. Associated Students Report. Senate agenda approved.